Rapid Surveillance for Vector Presence (RSVP): Development of a novel system for detecting Aedes aegypti and Aedes albopictus. - Brian L Montgomery; Martin A Shivas; Sonja Hall-Mendelin; Jim Edwards; Nicholas A Hamilton; Cassie C Jansen; Jamie L McMahon; David Warrilow; Andrew F van den Hurk (Public Library of Science (PLoS), 2017)
BACKGROUND:The globally important Zika, dengue and chikungunya viruses are primarily transmitted by the invasive mosquitoes, Aedes aegypti and Aedes albopictus. In Australia, there is an increasing risk that these species may invade highly urbanized regions and trigger outbreaks. We describe the development of a Rapid Surveillance for Vector Presence (RSVP) system to expedite presence- absence surveys for both species. METHODOLOGY/PRINCIPAL FINDINGS:We developed a methodology that uses molecular assays to efficiently screen pooled ovitrap (egg trap) samples for traces of target species ribosomal RNA. Firstly, specific real-time reverse transcription-polymerase chain reaction (RT-PCR) assays were developed which detect a single Ae. aegypti or Ae. albopictus first instar larva in samples containing 4,999 and 999 non-target mosquitoes, respectively. ImageJ software was evaluated as an automated egg counting tool using ovitrap collections obtained from Brisbane, Australia. Qualitative assessment of ovistrips was required prior to automation because ImageJ did not differentiate between Aedes eggs and other objects or contaminants on 44.5% of ovistrips assessed, thus compromising the accuracy of egg counts. As a proof of concept, the RSVP was evaluated in Brisbane, Rockhampton and Goomeri, locations where Ae. aegypti is considered absent, present, and at the margin of its range, respectively. In Brisbane, Ae. aegypti was not detected in 25 pools formed from 477 ovitraps, comprising ≈ 54,300 eggs. In Rockhampton, Ae. aegypti was detected in 4/6 pools derived from 45 ovitraps, comprising ≈ 1,700 eggs. In Goomeri, Ae. aegypti was detected in 5/8 pools derived from 62 ovitraps, comprising ≈ 4,200 eggs. CONCLUSIONS/SIGNIFICANCE:RSVP can rapidly detect nucleic acids from low numbers of target species within large samples of endemic species aggregated from multiple ovitraps. This screening capability facilitates deployment of ovitrap configurations of varying spatial scales, from a single residential block to entire suburbs or towns. RSVP is a powerful tool for surveillance of invasive Aedes spp., validation of species eradication and quality assurance for vector control operations implemented during disease outbreaks.